Shaping Future: Exploring Career Adaptability of Indonesian Students - Pratiwi, Tiara Iskandar; Supriatna, Mamat; Suherman, Uman; Sudrajat, Dadang (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
In an era of increasingly diverse, fragmented, and global careers, the ability to adapt and navigate one's development in the context of work is crucial. Career adaptability is a psychosocial construct that indicates an individual's readiness and resources to cope with current and future vocational development tasks, job transitions, and personal traumas. This study aims to examine the profile of career adaptability among students in Indonesia across various dimensions. This study employs a descriptive method and a saturated sample of 369 eleventh-grade students. The instrument used is the Career Maturity Inventory from-C (CMI-C) developed by Savickas & Porfeli (2011). The findings reveal (1) 58.5% of the students are in the mature category for career choice readiness, indicating that the students are adaptive in making career decisions and prepared to choose a job; (2) in the dimension of career concern, students are categorized as adaptive, (3) based on the dimensions of career curiosity and career confidence, students are categorized as non-adaptive, (4) based on the career consultation dimension, students are categorized as consultative. This study produces a hypothetical career guidance program to enhance students' career adaptability.